2017
DOI: 10.1002/qj.3010
|View full text |Cite
|
Sign up to set email alerts
|

Rain retrieval from dual‐frequency radar Doppler spectra: validation and potential for a midlatitude precipitating case‐study

Abstract: A recently developed technique retrieving the binned raindrop size distributions (DSDs) and air state parameters from ground-based K a and W-band radars Doppler spectra profiles is improved and applied to a typical midlatitude rain event. The retrievals are thoroughly validated against DSD observations of a 2D video disdrometer and independent X-band observations. For this case-study, profiles of rain rate, R, mean volume diameter and concentration parameter are retrieved, with low bias and standard deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…This study demonstrates that, for a stratiform case study characterized by strong evaporation, the profile of the raindrop size distributions (DSDs) retrieved by dual‐frequency K a ‐W band Doppler radars is consistent with independent observations of relative humidity. This result and the good performances in retrieving the DSDs at the ground [ Tridon et al , ] strongly suggest that such a technique allows for accurately profiling the evolution of the DSDs. In case of dry conditions, the knowledge of the vertical evolution of the DSD can be exploited in a twofold way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study demonstrates that, for a stratiform case study characterized by strong evaporation, the profile of the raindrop size distributions (DSDs) retrieved by dual‐frequency K a ‐W band Doppler radars is consistent with independent observations of relative humidity. This result and the good performances in retrieving the DSDs at the ground [ Tridon et al , ] strongly suggest that such a technique allows for accurately profiling the evolution of the DSDs. In case of dry conditions, the knowledge of the vertical evolution of the DSD can be exploited in a twofold way.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this issue, Tridon et al [] and Tridon and Battaglia [] have proposed a variational method (Optimal Estimation, OE) exploiting dual‐Doppler spectra at K a and W band to retrieve binned rain DSDs, vertical wind speed, and air broadening. The technique has been recently refined and extensively validated using a light precipitation event which occurred in Finland [ Tridon et al , ], the characteristics of which are very similar to the case study under examination. The retrieval is applied to KAZR data [ Matthews et al , ] and WSCAR data [ Matthews et al , ] in the region delimited by the black rectangle in Figure , between 19:32 and 19:57 UTC starting from the lowest available observations at W band (700 m above ground level, agl) up to 3.3 km asl in order to ensure that all particles are in the liquid phase.…”
Section: Strong Evaporation Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Tridon and Battaglia () have shown that the spectral broadening, due to air motion, could affect the Rayleigh plateau and bias the DSR measurements. To mitigate this, the optimal estimation method has been utilized (Tridon et al, ; Tridon et al, ; Tridon & Battaglia, ). After inspecting the cases analyzed in this paper (see the list in the supporting information), we found that the DSR in the Rayleigh region is rather flat and does not seem to be affected by the spectral broadening, which would skew the plateau (Tridon et al, ).…”
Section: Methodsmentioning
confidence: 99%